CAIRO’S AL-AZHAR PARK: MILLENIUM DEVELOPMENT GOALS ETCHED IN GREEN - el-Kishin, Khaled (PLANNING MALAYSIA, 2006)
This paper sheds light on a grand new park that has been inaugurated in Cairo on March 25’", 2005. The park is just one element of a far-reaching urban renewal scheme which seeks to restore a slum of Islamic Cairo where many cultural assets and monuments exist. The ambitious project, which has galvanized the nation, has drawn on the resources of international, national and local agencies in addition to grassroots organizations. Upon completion, the integrated development project is envisaged to rehabilitate many dwellings, monuments and urban spaces, in addition to creating employment, drawing droves of tourists and improving the quality of life in its vicinity. Thus, the impact of the project will most certainly fulfill some of the Millennium Development Goals (MDGs) set forth by the UN at the tum of the century.